Kurikulum dan Pendidikan (Merdeka Belajar Menurut Perspektif Humanism Arthur W Combs) - M Iqbal; Syaiful Anwar; Moh Maliki; Reskika Sari (Universitas Pendidikan Muhammadiyah Sorong, 2022)
The Republic of Indonesia aims to educate the nation's life, one example is by continuing to develop an educational curriculum, because a good curriculum is believed to have a great influence on improving the quality of education. Today, independent learning is the latest development of the curriculum used by Indonesia based on the idea of ​​the Ministry of Education and Culture. Seeing how independent learning is formed as a new curriculum, giving rise to different perspectives, this study uses the Literature study method. In the previous study regarding the view of freedom of learning in the perspective of processivism according to John Dewey, in this study we will discuss the freedom of learning in the perspective of humanism according to Arthur W. Combs, which basically has similarities in democratic education, these two views also give freedom to students. to think, but in progressivism tends to see students as part of the social, while humanism sees students as whole human beings who are individualists.